Moonbird : a year on the wind with the great survivor B95 - Hoose, Phillip M., 1947- (Farrar Straus Giroux, 2012)
Documents the survival tale of an intrepid shorebird who has endured annual migrations between Argentina and the Canadian Arctic throughout the course of a long lifetime while his species continues to decline.